A Robust Metal‐Organic Framework with Scalable Synthesis and Optimal Adsorption and Desorption for Energy‐Efficient Ethylene Purification. (6th March 2023) - Yu, Cong; Guo, Zhengdong; Yang, Lifeng; Cui, Jiyu; Chen, Sen; Bo, Yawen; Suo, Xian; Gong, Qihan; Zhang, Shang; Cui, Xili; He, Shengbao; Xing, Huabin
Abstract: Adsorptive separation is an energy‐efficient alternative, but its advancement has been hindered by the challenge of industrially potential adsorbents development. Herein, a novel ultra‐microporous metal‐organic framework ZU‐901 is designed that satisfies the basic criteria raised by ethylene/ethane (C2 H4 /C2 H6 ) pressure swing adsorption (PSA). ZU‐901 exhibits an "S" shaped C2 H4 curve with high sorbent selection parameter (65) and could be mildly regenerated. Through green aqueous‐phase synthesis, ZU‐901 is easily scalable with 99 % yield, and it is stable in water, acid, basic solutions and cycling breakthrough experiments. Polymer‐grade C2 H4 (99.51 %) could be obtained via a simulating two‐bed PSA process, and the corresponding energy consumption is only 1/10 of that of simulating cryogenic distillation. Our work has demonstrated the great potential of pore engineering in designing porous materials with desired adsorption and desorption behavior to implement an efficient PSA process. Abstract : A novel durable metal‐organic framework ZU‐901 with an ideal "S" shaped adsorption curve exhibits optimal adsorption and desorption behavior. It satisfies the basic criteria for potential industrial application: easy scale‐up, low cost, and high stability. Benefiting from the continuous rapid ethylene/ethane adsorption‐desorption performance, it is shown to be promising in the pressure‐swing adsorption of ethylene and ethane.